K-W-L: A TEACHING STRATEGY TO DEVELOP STUDENTS' READING COMPREHENSION IN THE SEVENTH GRADER OF JUNIOR HIGH SCHOOL : A Mixed Method Study - Khairunnisa, _ (2017)
Penelitian ini bertujuan untuk mengetahui penerapan strategi K-W-L dalam meningkatkan pemahaman membaca pada siswa kelas tujuh dan keterlibatan mereka di dalam kegiatan kelas. Penelitian ini menggunakan metode campuran. Terdapat dua kelas yang dijadikan sampel yaitu satu kelas kontrol dan satu kelas eksperimental. Setiap kelas terdiri dari 32 siswa. Data didapatkan dari hasil pre-test dan post-test, observasi kelas, catatan lapangan, dan interview. Hasil dari pre-test dan post-test menunjukkan bahwa terdapat sedikit peningkatan dari rata-rata kelas kontrol yaitu 11.41 (pre-test 28,75 dan post-test 40,16), sedangkan kelas eksperimental menunjukkan peningkatan yaitu sebesar 46,71 (pretest 30,16 dan post-test 75,31). Selain itu, nilai eta kuadrat adalah 0,725 yang mengindikasikan bahwa penerapan strategi K-W-L berpengaruh besar terhadap pemahaman bacaan siswa. Dapat disiratkan bahwa keterampilan pemahaman membaca siswa dapat dikembangkan melalui penerapan strategi K-W-L. Hasil dari observasi kelas, catatan lapangan, dan wawancara mengungkapkan bahwa setiap langkah strategi K-W-L berkontribusi untuk meningkatkan pemahaman membaca dan mengembangkan keterlibatan siswa dalam kegiatan di kelas.----- This study aims to investigate the implementation of K-W-L strategy to develop seventh graders students' reading comprehension and their involvement in the classroom activities. This study employed a mixed method design. There were two classes of seventh grade that were selected to be samples; one class of control group and one class of experimental group. Each of the class consisted of 32 students. The data were gained from the pre-test and post-test, the classroom observation, the field notes, and the interview. The results from the pre-test and post-test showed that there was a small increase of the mean of the control group which was 11.41 (pre-test 28.75 and the post-test 40.16), meanwhile, the experimental group showed a significant increase by 46.71 (pre-test 30.16 and the post-test 75.31). In addition, the value of eta squared was 0.725 which indicated that the implementation of K-W-L strategy had large effect on students' reading comprehension. It can be implied that the students' reading comprehension skill could be developed through the implementation of K-W-L Strategy. The results from the classroom observation, the field notes, and the interview revealed that each step of K-W-L strategy contributed to improve reading comprehension and develop students' involvement in the classroom activities.